Congenital Hypothyroidism: An Underestimated Clinical Entity (Medical Forum Monthly, 2024)
Objective: The aim of study was to determine the clinical features of Hypothyroid Children in various age groups residing in Rahim Yar Khan. Study Design: Prospective, descriptive, study, over a span of one year. Place and Duration of Study: This study was conducted in Pediatrics department at Sheikh Zayed Hospital and Medical College Rahim Yar Khan from 1st March 2010 to March 2011 . Materials and Methods: The thirty children of both sexes in age group of 1 day – 12 years presenting with clinical features, suspicion of Hypothyroidism were included in study. Children with subtle as well as full fledged sign and symptoms of hypothyroidism were considered for further evaluation. The clinical history, feeding pattern and clinical examination of these cases were recorded. Their blood was examined for T4, T3 and TSH. The X-rays of chest, X-rays of Skelton, particularly X-ray wrist and X-ray knee joint were obtained. Serum cholesterol, glucose, electrolytes (Na+ & K+) and perchlorate (KClO4) discharge test were obtained. Thyroid scintigraphy was done for isotope uptake. Ultrasonography for thyroid position, its size and detection of solid and cystic lesions was performed.Cardiac monitoring was gained by E.C.G. The data analysis was done by software SPSS 16. Results: All children with clinical features and investigations in favor of hypothyroidism were kept in four groups according to the age. The sluggish behavior, bradycardia, typical coarse faces and TSH in values above normal range were consistent findings in all thirty (n=30) cases. Conclusion: Congenital Hypothyroidism is usually under diagnosed that leads to mental retardation in a child. Therefore any child having suspicion of hypothyroidism should be evaluated by thyroid functions test (TFT), including new born screening.